2021
DOI: 10.5014/ajot.2021.046813
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of COVID-19 on Occupational Therapists: An Online Survey in Japan

Abstract: Importance: Coronavirus disease 2019 (COVID-19) has had a severe psychological impact on frontline and second-line medical workers. However, few empirical reports have been published on its impact on occupational therapists. Clarifying the mental health status of occupational therapists is important to maintain care quality and prevent psychological problems in this population.Objective: To investigate the psychological impact of COVID-19 on Japanese occupational therapists in prefectures with and without seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 32 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…Based on our previous study (6), we focused on differences in field-specific impacts on the psychological aspects of anxiety, depression, insomnia, and loneliness. To assess each psychological aspect, we used four validated questionnaires: the Zung Self-Rating Anxiety Scale (SAS) (28), Zung Self-Rating Depression Scale (SDS) (29), Japanese version of the Insomnia Severity Index (ISI-J) (30,31) and Japanese version of the three-item loneliness scale (TILS) (32).…”
Section: Psychological Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous study (6), we focused on differences in field-specific impacts on the psychological aspects of anxiety, depression, insomnia, and loneliness. To assess each psychological aspect, we used four validated questionnaires: the Zung Self-Rating Anxiety Scale (SAS) (28), Zung Self-Rating Depression Scale (SDS) (29), Japanese version of the Insomnia Severity Index (ISI-J) (30,31) and Japanese version of the three-item loneliness scale (TILS) (32).…”
Section: Psychological Measurementmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has had an unprecedented impact on society and led to a dramatic loss of human life worldwide, presenting a unique challenge to public health and socioeconomic welfare (1,2). The repeated waves of COVID-19 outbreaks have resulted in social isolation (2), loss of accessibility (3), economic crises (4), substance abuse (5), and deterioration of the working environment (4,(6)(7)(8), which are reported to be closely related to the mental health of citizens and workers. In particular, many previous studies have reported and heavy workload on OTs, no study has investigated the differences in the impact of the COVID-19 pandemic on work life among OTs working in different fields.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological impacts of COVID-19 on second-line healthcare professionals have been documented (5)(6)(7)(8). Occupational therapists are classified as second-line medical professionals who do not directly care for patients with COVID-19 during the early stages (9).…”
Section: Introductionmentioning
confidence: 99%
“…The increased workload and working hours negatively impact mental health conditions (6,(26)(27)(28)(29)(30). For example, previous literature showed that workload is positively related to depression and that its relationship was mediated by emotional distress (29), and long working hours are also associated with depression (31) and further associated with poor patient safety and decreased care quality (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation